(untitled) (Journal of the College of Basic Education, 2023)
The Arabic language received the utmost attention of its children and their continuous efforts to preserve theits integrity and touch the aspects of indication of the different meanings in the word and the sentence and the composition and show whatLearn about the single word or when it combines with its sisters in speech, so the studies were numerous and varied.Research in various branches of language, including morphology, which caught my eye (chapter of genealogy).You found me concerned with clarifying something of what our ancient scholars meant, and with an attempt to benefit from the lesson.Modern Morphology in dealing with its issues. Thus, the topics of this research wereThe traditional study and the contemporary study The nature of the research necessitated that it fall into four clearer chapters.The first is lineage, and the changes that occur to the attributed name. The second chapter includes threeTopics dealt with the lineage of what ended with the feminine gender, and what ended with the alif, and what ended with the hamza.The third chapter, in its three discussions, studied the attribution to the imperfect noun, to the dual and the plural,And to the compound noun, while the fourth chapter discusses four topics related to what is concluded with B.stressing, and to what was on fa’il, fa’il, fa’ila, fa’ila, fa’oul and fa’ula, and to the omitted nounFrom it some of its origins to what was put on two letters.